Website Prototype Design Animation Study Program Based Content Management System Wordpress - Charles De Haan (Institute of Computer Science (IOCS), 2022)
The availability of information through information and communication technology (ICT) in the world of education is not only supported in operations but has become a necessity and an obligation that must be implemented. One of the application products on the internet that utilizes the development of communication and information technology is a website application. The problem of the lack of information from the main website for animation study program students, plus the Covid-19 pandemic which requires online lectures, causes direct communication and submission of data or documents from study program management to students will experience several problems. We need a website that can bridge the information needs. the most possible way, and can quickly be developed is to use a Web Content Management System. The website is developed in an initial form or often called a prototype, by submitting a questionnaire to prospective website users. The goal is to obtain an overview of what information should be on the website. The results of this study are in the form of a website prototype for an animation study program that is relevant to the needs of users, namely lecturers, students, and the general public.